Diagnostic and prognostic role of Ki-67 and cytokeratin-5 expression in BPH and carcinoma prostate - Bakna, Minu; Malik, Reeni; Jain, Pramila; Jain, Rashmi; Jain, Ankit (International Journal of Medical Research and Review, 2016)
Background: Cytokeratin-5 which stains the basal cell layer of the of the prostatic glands and Ki-67 which is a proliferation marker and stains the proliferative population of the lesion has been employed as markers of two different categories viz. basal cell marker and proliferative markers respectively in various studies. Aim of this study was to evaluate the utility of cytokeratin-5 and Ki-67 in differentiating and diagnosing the benign lesion like Benign prostatic hyperplasia and malignant lesion i.e. Carcinoma Prostate. Material and Methods: 90 cases of prostatic adenocarcinoma, BPH and prostatic inflammatory conditions were taken. Immunohistochemical staining for Ki67 and CK-5 was performed along with appropriate positive controls for each marker. Ki67 scoring classified as Negative, Low grade & High grade. Cytokeratin-5 scoring classified as Diffuse, Focal & Negative. Results: Cytokeratin-5 expression was found positive in 96.71% cases of BPH. Out of these 78.68% cases were diffusely positive and 18.03% cases were focal positive. Expression of Cytokeratin-5 in Carcinoma Prostate was 40%, 6.66% and 0% in well, moderate and poorly differentiated carcinomas respectively, whereas no expression of the marker in 60%, 93.33% and 100% cases of well, moderate and poorly differentiated carcinomas respectively. Ki-67 showed low grade expression in mere 8.20% cases of BPH. In Carcinoma Prostate Ki67 expression was shown by 60%, 79% and 100% cases of well, moderate and poorly differentiated carcinomas respectively. Conclusion: Diffuse Cytokeratin-5 expression was found in majority of BPH cases, while maximum Carcinoma prostate cases were negative. Ki-67 expression was found positively correlated with increasing Gleason’s grade in carcinoma prostate, while expression in benign lesion was not significant.